2016
DOI: 10.1016/j.techfore.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

The influence of international research interaction on national innovation performance: A bibliometric approach

Abstract: International research interactions (IRIs), specifically co-invention, co-assignment and the international appropriation of inventions, are increasing as a result of globalization and rising technological complexity. Yet the impact of IRIs on national innovation performance is ambiguous. In this study patent-based bibliometric indicators are developed to investigate the influence of IRIs on innovation performance using bibliometric and statistical data covering six knowledge intensive sectors and 32 countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
1
13
0
1
Order By: Relevance
“…In addition, according to the perception adopted in innovative models, internationalization is perceived as an innovation and thus the development of innovation opens market opportunities. Our results enrich the existing research and complement the only bibliometric literature review conducted by Stek and van Geenhuizen (2016) related to the investigated subject.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, according to the perception adopted in innovative models, internationalization is perceived as an innovation and thus the development of innovation opens market opportunities. Our results enrich the existing research and complement the only bibliometric literature review conducted by Stek and van Geenhuizen (2016) related to the investigated subject.…”
Section: Resultssupporting
confidence: 76%
“…Finally, the only bibliometric literature review, applied by Stek and van Geenhuizen (2016) in the Netherlands, which is a good supplement to our literature review, included the impact of international research interactions on national innovation performance. The second paper from the Netherlands authored by Tijssen (2004) presents a review of corporate articles concerning the commercialization of scientific research.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…The SLR technique was used to map the studies conducted on this subject. The research questions were defined ex-ante based on the literature, which established a relationship between innovation and performance (Denmark; Ali et al, 2016;Fixari & Pallez, 2016;Hojnik & Ruzzier, 2016;Laursen & Foss, 2003;Li et al, 2016;Oura et al, 2016;Park, 2016;Powell & Snellman, 2004;Rocha, 2015;Stek & van Geenhuizen, 2016). An SLR analysis was conducted along with the systematization of a research protocol (see Figure 1), serving as an instrument with the methodological rigor required to validate and propose a structured knowledge base for decision makers and research analysts (Tranfield, Denyer, & Smart, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies on innovation and performance have been carried out due to their relevance for both private and public organizations (Archibugi & Filippetti, 2018;Laursen & Foss, 2003;Laursen & Salter, 2006;Powell & Snellman, 2004;Stek & van Geenhuizen, 2016). The empirical evidence has shown that innovative companies tend to achieve higher performance in the same way that countries that invest public resources to develop innovation also improve conditions for economic development (Powell & Snellman, 2004;Taalbi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a practical implication, the paper underlines the benefits of ambidexterity and the multifaceted role of government within the business network, requiring the focal organisation to re-consider its interactions with various government departments and other agencies. Stek and van Geenhuizen (2016) emphasised the importance on international research interactions, specifically interpersonal collaboration, institutional collaboration and within multinational corporation collaboration as a result of globalisation and rising technological complexity. In their study, patent-based bibliometric indicators are developed to investigate the influence of different types of IRI on innovation performance using bibliometric data covering eight knowledge intensive manufacturing sectors and 32 countries during the 2003-2008 period.…”
Section: Introductionmentioning
confidence: 99%